It came from something awful : how a toxic troll army accidentally memed Donald Trump into office - Beran, Dale (All Points Books, 2019)
The internet has transformed the ways we think and act, and by consequence, our politics. The most impactful recent political movements on the far left and right started with massive online collectives of teenagers. Strangely, both movements began on the same website: an anime imageboard called 4chan.org. It Came from Something Awful is the fascinating and bizarre story of 4chan and its profound effect on youth counterculture. Dale Beran has observed the website's shifting activities and interests since the beginning. 4chan is a microcosm of the internet itself<U+2015>simultaneously at the vanguard of contemporary culture, politics, comedy and language, and a new low for all of the above. It was the original meme machine, mostly frequented by socially awkward and disenfranchised young men in search of a place to be alone together. During the recession of the late 2000<U+2019>s, the memes became political. 4chan was the online hub of a leftist hacker collective known as Anonymous and a prominent supporter of the Occupy Wall Street movement. But within a few short years, the site<U+2019>s ideology spun on its axis; it became the birthplace and breeding ground of the alt-right. In It Came from Something Awful, Beran uses his insider<U+2019>s knowledge and natural storytelling ability to chronicle 4chan's strange journey from creating rage-comics to inciting riots to<U+2015>according to some<U+2015>memeing Donald Trump into the White House.